37. Dysphagia in Myotonic Dystrophy type 1: Preliminary results of an integrated neurophysiological and swallowing protocol. Issue 4 (April 2016) - Raimondi, E.; Zardoni, M.; Bruno, S.; Nascimbene, C.; Pasanisi, M.B.; Morandi, L.; Gianelli, F.; Colombo, M.; Schindler, A.; Mariani, C.; Osio, M.
Abstract : Dysphagia is common and under-diagnosed in Myotonic Dystrophy (DM1), leading to nutritional derangement and ab-ingestis pneumonia. We tried to define the prevalence of dysphagia and to understand underlying mechanisms through an integrated swallowing evaluation on DM1 patients. Our protocol includes: laryngeal accelerometric sensor, submental and cricopharyngeal (CP) muscles EMG to evaluate Dysphagia Limit (DL) (volume at which a second swallow becomes necessary to swallow a water bolus) and swallowing jitter; needle EMG of genioglossus muscle (G-EMG); fiberoptic endoscopic swallowing evaluation (FEES), clinical swallowing scales. Our results in 10 DM1 patients (6M-4F, mean age 46 ± 10), compared to 6 healthy subjects (3M-3F, mean age 30 ± 3), showed myotonic discharges (9/10 patients) in G-EMG; reduction in DL in all DM1 patients; abnormal swallowing jitter in 6/10 patients, with 5 of them showing anomalies in temporal features of the swallowing reflex; myotonia in CP muscle in 3 patients. 2 patients did not show dysphagia at FEES; penetration signs were present in 4 and 5 patients respectively with liquids and semisolids. Our data confirm that swallowing problems are common in DM1. DL and swallowing jitter are the most sensitive altered parameters in these patients. We are extending this protocol to a larger cohort of patients.